Preparation method and application of erbium-doped hollow tubular g-C3N4 photocatalyst

Through erbium doping and the construction of hollow tubular morphology modified g-C3N4 photocatalysts, the existing photocatalysts have been solved, and the problem of low light utilization efficiency and difficulty in activate PMS is achieved, achieving a more efficient degradation effect of organic pollutants.

CN119793504APending Publication Date: 2025-04-11TIANJIN POLYTECHNIC UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411773860.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing g-C3N4 photocatalysts have low light utilization efficiency, slow carrier migration, and difficulty in activation of persulfate (PMS), which limits their application efficiency in water treatment.

Method used

By erbium doping and building hollow tubular morphology, the g-C3N4 photocatalyst is modified to improve its photocatalytic efficiency and activation ability of PMS.

Benefits of technology

The electronic structure utilization of the photocatalyst is improved, and the degradation efficiency of organic pollutants is enhanced, especially when used in coupling with PMS, which significantly improves the degradation rates of lonoxicam and tetracycline.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793504A_ABST
    Figure CN119793504A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of semiconductor photocatalyst preparation and environmental protection, and discloses a preparation method and application of an erbium-doped hollow tubular g-C3N4 photocatalyst (Er-CN). The preparation method comprises the following steps: firstly, preparing a catalyst precursor by taking melamine and erbium acetate as raw materials by adopting a hydrothermal synthesis method, and then preparing the erbium-doped hollow tubular g-C3N4 photocatalyst (Er-CN) by adopting a high-temperature calcination method. The preparation method is simple in equipment and convenient to operate, and materials are easy to obtain and low in cost. The prepared photocatalyst has a very good effect in the aspect of coordinating with persulfate to treat pollutants in a water body, so that the photocatalyst has a good application prospect and value in the field of environmental wastewater treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of semiconductor catalysts, in particular to a method for preparing an erbium-doped hollow tubular g-C3N4 photocatalyst (Er-CN) and its application in photocatalytic degradation of lornoxicam (LC) and tetracycline (TC) using a single photocatalyst or coupling with persulfate, and belongs to the field of environmental protection. Background Art

[0002] Micropollutants (such as antibiotics, drugs, and personal care products) can have serious impacts on ecosystems and human health even at extremely low concentrations in the environment. These substances are difficult to be completely removed by traditional sewage treatment processes. Long-term accumulation will interfere with the metabolic activities of microorganisms in water bodies, leading to the spread of drug-resistant genes, threatening ecological balance and public health. For example, tetracycline, as a commonly used antibiotic, will lead to an increase in antibiotic-resistant bacteria in the water environment after widespread discharge, affecting the physiological functions of aquatic organisms; lornoxicam is an anti-inflammatory drug that can accumulate in organisms and have toxic effects on the endocrine system and liver function of aquatic organisms, endangering the safety of the food chain. Therefore, it is particularly important to balance the clinical advantages of these drugs with environmental risks. Further research and development of more efficient water treatment technologies are needed to promote the degradation and removal of drug pollutants, thereby reducing their environmental load and ensuring the sustainability of drug use.

[0003] The combination of semiconductor photocatalysis and peroxymonosulfate (PMS) is an advanced oxidation technology that activates PMS to generate highly active free radicals (such as sulfate radicals SO4 -· and hydroxyl radicals ·OH). These strong oxidizing free radicals can effectively decompose organic pollutants in water and further enhance the degradation efficiency of pollutants. The introduction of PMS not only improves the reaction rate of photocatalysis, but also broadens the application range of photocatalysts, making them still have good catalytic performance under weaker light sources, which shows good application prospects in water treatment and pollutant removal. Graphitic carbon nitride (g-C3N4) is an excellent carbon-based material, which is used in many fields because of its low price, high stability and non-toxicity. However, the photocatalytic efficiency of g-C3N4 is severely limited by its inherent defects, such as slow carrier migration and fast recombination of photogenerated electron-hole pairs. At the same time, it is difficult to activate PMS due to its poor electron transport ability. Therefore, by modifying g-C3N4, not only the photocatalytic efficiency of g-C3N4 can be improved, but also the activation ability of PMS can be improved. The modification methods of g-C3N4 include element doping, forming heterostructures with other semiconductors, and constructing micromorphology. Element doping includes metal doping and non-metal doping, which can further effectively improve g-C3N4 by changing the chemical properties of g-C3N4, narrowing the band gap, adjusting the electronic structure, etc. The construction of micro-morphology is to increase the specific surface area and increase the active sites by changing the original morphology and constructing a 2D / 3D micro-morphology, thereby improving the photocatalytic efficiency.

[0004] The present invention adopts the method of doping erbium element and constructing tubular morphology to improve the photocatalytic efficiency of g-C3N4. The rare earth element erbium has a unique f orbital electronic structure and can provide multiple energy level transition pathways. This complex electronic transition ability can effectively absorb light energy in a wide wavelength range, especially in the visible light and near-infrared region. At the same time, erbium-doped carbon nitride can adjust its energy band structure and reduce the band gap, so that it can absorb light energy more effectively. Therefore, in the case of rare earth doping, the electronic structure of the photocatalyst is adjusted, so that its utilization rate of light energy is higher, thereby improving the catalytic reaction rate and helping to degrade pollutants more efficiently. In addition, the rare earth element erbium has a high surface activity and can increase the adsorption capacity of carbon nitride for organic pollutants. Therefore, the present invention adopts erbium-doped hollow tubular g-C3N4 photocatalyst to improve the photocatalytic activity, which can degrade pollutants more efficiently. Summary of the invention

[0005] [Technical issues]

[0006] Aiming at the shortcomings of low light utilization efficiency and too fast recombination velocity of photogenerated carriers of g-C3N4, a preparation scheme of Er-CN is provided. The preparation scheme has low implementation cost and the raw materials are simple and easy to obtain.

[0007] [Technical solution]

[0008] In order to achieve the above object, a method for preparing Er-CN is provided through an embodiment of the present invention, and the preparation scheme comprises the following steps:

[0009] (1) Preparation of Er-doped Hollow Tubular g-C3N4 Photocatalyst (Er-CN) Precursor

[0010] Melamine was dissolved in deionized water according to a certain ratio, heated and stirred at 90°C until dissolved to obtain a melamine clear solution. Erbium acetate (0.10 g, 0.15 g, 0.20 g, 0.25 g) was added to the dissolved melamine solution, stirred until dissolved, and then transferred to a polytetrafluoroethylene stainless steel autoclave, heated at 180°C for 24 hours to obtain a photocatalyst precursor.

[0011] (2) Preparation of Er-CN photocatalyst

[0012] The precursor powder was placed in a crucible, covered with a lid and placed in a tube furnace. Under the protection of inert gas, the temperature was raised to 550°C at a rate of 5°C / min and kept at this temperature for 4 hours to obtain an Er-CN photocatalyst.

[0013] In the step (1), melamine and deionized water are prepared in an arbitrary ratio of 1 g:60 mL; the mass ratio of erbium acetate to melamine is (0.10 g, 0.15 g, 0.20 g, 0.25 g): 4 g.

[0014] In the step (1), the temperature for heating and stirring until the mixture is dissolved is 70°C to 100°C; the heating condition in the polytetrafluoroethylene stainless steel autoclave is 180°C to 200°C;

[0015] In the step (1), the heating time in the polytetrafluoroethylene stainless steel autoclave is 20 h to 28 h;

[0016] In the step (2), the inert gas in the tube furnace is N2 or Ar;

[0017] In the step (2), the heating rate of the tube furnace is 1°C / min to 5°C / min;

[0018] In the step (2), the heating temperature in the tube furnace is 500° C. to 600° C.;

[0019] In the step (2), the tubular furnace is kept warm for 3 to 5 hours.

[0020] Material Source

[0021] Melamine and erbium acetate were of analytical grade and purchased from Aladdin Chemical Reagent Co., Ltd.

[0022] [Beneficial Effects]

[0023] In summary, the present invention has the following beneficial effects:

[0024] The present invention realizes the preparation of erbium-doped hollow tubular g-C3N4 photocatalyst, the Er-CN band gap becomes smaller, the visible light absorption range is expanded, and the separation efficiency of photogenerated electron-hole pairs in carbon nitride is improved. The effect of adding different erbium acetate masses on the activity of the photocatalyst is investigated, and the activity of the composite photocatalyst is confirmed by degrading LC and TC. The experimental results show that when the mass of erbium acetate added is 0.2g, the Er-CN-3 photocatalyst exhibits higher photocatalytic activity, and the degradation rates of LC and TC within 90min reach 86.1% and 76.43%, respectively. More importantly, after adding PMS, the degradation rates of LC and TC within 30min reach 97.85.1% and 78.97%, respectively. Its main mechanism is that under visible light irradiation, the catalyst is excited to generate a large number of holes (h + ) and electron (e - ). On the one hand, h on the valence band + Can oxidize OH - Generate ·OH, e on the conduction band - Can be reduced with O2 in water to generate O2 - On the other hand, Er-CN excites electron-hole pairs under light, activating PMS to generate highly active free radicals (such as sulfate radicals SO4 - · and hydroxyl radicals ·OH). These strong oxidizing free radicals can effectively decompose organic pollutants in water, further enhancing the degradation efficiency of pollutants. It is more helpful to activate PMS to generate more active groups to degrade organic pollutants. At the same time, the Er-CN prepared by this method has a stable structure, simple and easy-to-obtain raw materials, and a simple operation process. It is a green and environmentally friendly technology with high efficiency and low waste. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the electron microscope image of Er-CN.

[0026] Figure 2 The kinetic curve and degradation rate diagram of LC degradation by Er-CN under different illumination times.

[0027] Figure 3 The kinetic curve and degradation rate diagram of LC degradation by Er-CN coupled with PMS under different illumination times.

[0028] Figure 4 The kinetic curve and degradation rate diagram of TC degradation by Er-CN under different illumination times.

[0029] Figure 5The kinetic curve and degradation rate diagram of TC degradation by Er-CN coupled with PMS under different illumination times.

[0030] Figure 6 This is a graph showing the stability of Er-CN-3 against LC degradation.

[0031] Figure 7 This is the experimental diagram of the stability of Er-CN-3 against TC degradation.

[0032] Figure 8 This is the bandgap width diagram of g-C3N4 and Er-CN. DETAILED DESCRIPTION

[0033] Evaluation of the photocatalytic activity of the photocatalyst prepared in the present invention: ① Single catalyst degradation of pollutants: Take 50 mg of erbium-doped photocatalyst and add them to 100 mL of 20 mg / L lornoxicam or tetracycline solution, and irradiate them with a 220WXe lamp for 90 minutes after dark adsorption for 30 minutes. Take samples every 10 minutes during the illumination process and take the supernatant; ② Catalyst and PMS coupling degradation of pollutants: Take 50 mg of erbium-doped photocatalyst and add them to 100 mL of 20 mg / L lornoxicam and tetracycline solution, and add 0.015 g of potassium persulfate (PMS) after dark adsorption for 30 minutes. Then, irradiate them with a 220WXe lamp for 30 minutes. Take samples every 10 minutes during the illumination process and take the supernatant. max =376nm and λ max =350nm, and the degradation rate Dr is calculated by the formula: Dr = (C0-C) × 100 / C0, where C0 is the initial concentration, C is the concentration of lornoxicam or tetracycline solution measured at time t, and t is the reaction time.

[0034] In order to enable those skilled in the art to more clearly understand the present invention, the present invention is further described in detail below in conjunction with the examples. However, it should be understood that the following examples are only preferred embodiments of the present invention, and the scope of protection claimed by the present invention is not limited thereto.

[0035] Embodiment 1:

[0036] The Er-CN according to the present invention is prepared by the following method:

[0037] (1) 4 g of melamine was dissolved in 240 mL of deionized water and stirred at 90° C. until completely dissolved; 0.10 g of erbium acetate was added to the dissolved melamine solution and stirred until dissolved; the melamine clear solution was transferred into a polytetrafluoroethylene stainless steel autoclave and heated at 180° C. for 24 h; the sample was washed and dried to obtain an Er-CN-1 photocatalyst precursor.

[0038] (2) The precursor powder was placed in a crucible, covered with a lid and placed in a tube furnace. Under N2 protection, the temperature was increased at a rate of 5°C / min to 550°C and kept at this temperature for 4 h to obtain the Er-CN-1 photocatalyst.

[0039] Embodiment 2:

[0040] The same steps as in Example 1 were followed, except that 0.15 g of erbium acetate was added to the dissolved melamine solution in (1) and stirred until dissolved; the melamine solution was transferred into a polytetrafluoroethylene stainless steel autoclave and heated at 180° C. for 24 h; the sample was washed and dried to obtain an Er-CN-2 photocatalyst precursor. Finally, the Er-CN-2 photocatalyst was obtained through step (2).

[0041] Embodiment 3:

[0042] The same steps as in Example 1 were followed, except that 0.20 g of erbium acetate was added to the dissolved melamine solution in (1) and stirred until dissolved; the melamine solution was transferred into a polytetrafluoroethylene stainless steel autoclave and heated at 180° C. for 24 h; the sample was washed and dried to obtain an Er-CN-3 photocatalyst precursor. Finally, the Er-CN-3 photocatalyst was obtained through step (2).

[0043] Embodiment 4:

[0044] The same steps as in Example 1 were followed, except that 0.25 g of erbium acetate was added to the dissolved melamine solution in (1) and stirred until dissolved; the melamine solution was transferred into a polytetrafluoroethylene stainless steel autoclave and heated at 180° C. for 24 h; the sample was washed and dried to obtain an Er-CN-4 photocatalyst precursor. Finally, the Er-CN-4 photocatalyst was obtained through step (2).

[0045] Embodiment 5:

[0046] ① The degradation effects of the catalyst prepared by the same steps as in Examples 1-4 above on LC and TC within 90 min are shown in Table 1.

[0047] ② After adding PMS to the catalyst prepared by the same steps as in Examples 1-4 above, the synergistic effect of the catalyst and PMS on the degradation of LC and TC within 30 minutes is shown in Table 1.

[0048] After Examples 1-4 were coupled with PMS, the photocatalytic degradation effects on the two pollutants were significantly improved, among which the degradation efficiency of Example 3 on the two pollutants after coupling with PMS was twice that of a single catalyst.

[0049] Table 1 Degradation effects of different embodiments on different pollutants

[0050]

Claims

1. A preparation method and application of erbium-doped hollow tubular g-C3N4 photocatalyst, characterized in that: The preparation method steps are as follows: (1) Preparation of Er-doped Hollow Tubular g-C3N4 Photocatalyst (Er-CN) Precursor Melamine was dissolved in deionized water according to a certain ratio, heated and stirred at 90°C until dissolved to obtain a melamine clear solution. Erbium acetate (0.10 g, 0.15 g, 0.20 g, 0.25 g) was added to the dissolved melamine solution, stirred until dissolved, and then transferred to a polytetrafluoroethylene stainless steel autoclave, heated at 180°C for 24 hours to obtain a photocatalyst precursor. (2) Preparation of Er-CN photocatalyst The precursor powder was placed in a crucible, covered with a lid and placed in a tube furnace. Under the protection of inert gas, the temperature was raised to 550°C at a rate of 5°C / min and kept at this temperature for 4 hours to obtain an Er-CN photocatalyst.

2. The preparation method and application of an erbium-doped hollow tubular g-C3N4 photocatalyst according to claim 1, characterized in that: The step (1) is as follows: melamine and deionized water are mixed in any ratio of 1 g:60 mL. The mass ratio of erbium acetate to melamine is (0.10 g, 0.15 g, 0.20 g, 0.25 g):4 g.

3. The preparation method and application of an erbium-doped hollow tubular g-C3N4 photocatalyst according to claim 1, characterized in that: The step (1) is: heating and stirring until the dissolving temperature is 70°C to 100°C. The heating condition in the polytetrafluoroethylene stainless steel autoclave is 180°C to 200°C.

4. The preparation method and application of an erbium-doped hollow tubular g-C3N4 photocatalyst according to claim 1, characterized in that: The step (1) is as follows: the heating time in a polytetrafluoroethylene stainless steel autoclave is 20 hours to 28 hours.

5. The preparation method and application of an erbium-doped hollow tubular g-C3N4 photocatalyst according to claim 1, characterized in that: The step (2) is as follows: the inert gas in the tube furnace is N2 or Ar.

6. The preparation method and application of an erbium-doped hollow tubular g-C3N4 photocatalyst according to claim 1, characterized in that: The step (2) is as follows: the heating rate of the tubular furnace is 1°C / min to 5°C / min.

7. The preparation method and application of an erbium-doped hollow tubular g-C3N4 photocatalyst according to claim 1, characterized in that: The step (2) is as follows: the heating temperature in the tubular furnace is 500° C. to 600° C.

8. The preparation method and application of an erbium-doped hollow tubular g-C3N4 photocatalyst according to claim 1, characterized in that: The step (2) is as follows: the tubular furnace is kept warm for 3 hours to 5 hours.

9. The method for preparing the Er-CN composite photocatalyst according to claim 1, characterized in that: The prepared Er-CN composite photocatalyst is applied to degrade lornoxicam (LC) and tetracycline (TC) in wastewater.